The Moderating Role of Disaster Memorial Facilities on the Relationship Between Threat Appraisal, Fear, and Information Sources Toward Protection Motivation: A Case Study of Indonesian People Living on Japan’s Tohoku Coast - Cahyanti, Mega Mirasaputri (Journal of disaster research, 2025)
The 2011 Great East Japan Earthquake and tsunami, which devastated much of northeast Japan (Tohoku), underscored the failure of many residents to evacuate in time. To mitigate similar tragedies in the future, the region established disaster memorial facilities (DMFs) to convey the lessons learned from the disaster. This study evaluates the effectiveness of these DMFs using the Protection Motivation Theory framework to analyze the protective actions taken by individuals who have never experienced a tsunami. A structural equation modeling analysis, conducted using Amos 28, was employed to evaluate and substantiate novel conceptual theories through a multigroup analysis. The findings can be summarized as follows: (1) the source of information has a significant effect on threat appraisal; (2) threat appraisal significantly influences evacuation motivation; and (3) threat appraisal has a significant impact on fear of fatality. A significant difference exists between respondents who have visited DMFs and those who have not. This study suggests that individuals who have visited DMF sites tend to acquire significant insights that motivate them to evacuate promptly in the event of a potential tsunami. Conversely, those without such experiences are less influenced by the information they receive, potentially leading to a lower motivation to evacuate.